SOLUBILITY ENHANCEMENT AND DISSOLUTION IMPROVEMENT- LIQISOLID TECHNIQUE - Kapoor, D; Sharma, S; Patel, M; Vyas, R B; Chaitali, Lad (Journal of Drug Delivery and Therapeutics, 2013)
This technique is based upon the admixture of drug loaded solutions with appropriate carrier and coating materials. The use of non-volatile solvent causes improved wettability and ensures molecular dispersion of drug in the formulation and leads to enhance solubility. By using hydrophobic carriers (non-volatile solvents) one can modify release (sustained release) of drugs by this technique. Liquisolid system is characterized by flow behavior, wettability, powder bed hydrophilicity, saturation solubility, drug content, differential scanning calorimetry, Fourier transform infra red spectroscopy, powder X-ray diffraction, scanning electron microscopy, in-vitro release and in-vivo evaluation. The increased bioavailability is due to either increased surface area of drug available for release, an increased aqueous solubility of the drug, or improved wettability of the drug particles. According to the new formulation method of liqui-solid compacts, liquid medications such as solutions or suspensions of water insoluble drugs in suitable nonvolatile liquid vehicles can be converted into acceptably flowing and compressible powders by blending with selected powder excipients. It has been speculated that such systems exhibit enhanced release profiles. In this case, even though the drug is in a solid dosage form, it is held within the powder substratin solution or, in a solubilized, almost molecularly dispersed state, which contributes to the enhanced drug dissolution properties. According to the new formulation method of liquisolid compacts, liquid medications such as solutions or suspensions of water insoluble drugs in suitable non-volatile liquid vehicles can be converted into acceptably flowing and compressible powders by blending with selected powder excipients. Large scale production of fabricated drug on commercial level successful liquisolid tablet is a determination of optimal flowable liquid retention. Keywords: Poorly soluble drugs, coating material, carrier, hydrophilic solvent, liquisolid compacts